2022-RA-903-ESGO Prophylactic radical fimbriectomy with delayed oophorectomy in women with a high risk of developing an ovarian carcinoma: results of a prospective phase 2 national study. (20th October 2022) - Leblanc, Eric; Narducci, Fabrice; Hajj, Houssein El; Ferron, Gwenael; Mailliez, Audrey; Charvolin, Jean-Yves; Gomez, Calos Martinez; Guyon, Frederic; Lemaire, Anne Sophie; Fourchotte, Virginie; Probst, Alicia; Lambaudie, Eric; et al.
Abstract : Introduction/Background: Risk-reducing salpingo-oophorectomy is the gold standard for prophylaxis of ovarian cancer in high-risk women. Due to significant adverse effects, 20–30% of women delay or refuse early oophorectomy. We proposed a new two-step risk-reducing procedure: radical fimbriectomy followed by delayed oophorectomy, which is evaluated by the current RF/DO Phase 2 trial (NCT01608074 ). Methodology: Pre-menopausal women ≥35 years with HBOC who refused RRSO were offered to participate in RF/DO trial. All surgical specimens underwent the SEE-FIM protocol. The primary endpoint was the cumulative incidence of ovarian/pelvic invasive carcinoma. Secondary endpoints were morbidity, surgical specimen abnormalities, menopause, breast cancer (BC) occurrence, and secondary oophorectomy. Results: From January 2012 to October 2014, 121 patients underwent RF, 51 were performed in the ambulatory setting. Occult neoplasia was found in two cases, with one tubal HGSC. Two patients experienced grade-1 intraoperative complications. No early or delayed grade≥3 postoperative complications. After 7.3 years of median follow-up, no cases of pelvic invasive cancer were noted. 3/52 patients developed de novo BC. One BRCA1-mutated woman delivered safe twins. 25 patients underwent menopause including 15 who had received chemotherapy for BC: 23 before DO and two did not undergo DO. Overall, 46 women underwent DO, 23 after menopause, 3 after the age of 51, 8 for personal decision, and 11 for other medical reasons. No abnormalities were found in any DO specimens. Conclusion: RF/DO appears a safe and well-tolerated risk-reducing approach that avoids early menopause for HBOC patients. Furthermore, due to the absence of abnormalities at mesothelio-Müllerian junctions, simple total bilateral salpingectomy may replace RF